Investigational prostaglandin D2 receptor antagonists for airway inflammation. (2nd June 2016) - Santini, Giuseppe; Mores, Nadia; Malerba, Mario; Mondino, Chiara; Macis, Giuseppe; Montuschi, Paolo
ABSTRACT: Introduction: By activating DP1 and DP2 receptors on immune and non-immune cells, prostaglandin D2 (PGD2 ), a major metabolic product of cyclo-oxygenase pathway released after IgE-mediated mast cell activation, has pro-inflammatory effects, which are relevant to the pathophysiology of allergic airway disease. At least 15 selective, orally active, DP2 receptor antagonists and one DP1 receptor antagonist (asapiprant) are under development for asthma and/or allergic rhinitis. Areas covered: In this review, the authors cover the pharmacology of PGD2 and PGD2 receptor antagonists and look at the preclinical, phase I and phase II studies with selective DP1 and DP2 receptor antagonists. Expert opinion: Future research should aim to develop once daily compounds and increase the drug clinical potency which, apart from OC000459 and ADC-3680, seems to be relatively low. Further research and development of DP2 receptor antagonists is warranted, particularly in patients with severe uncontrolled asthma, whose management is a top priority. Pediatric studies, which are not available, are required for assessing the efficacy and safety of this novel drug class in children with asthma and allergic rhinitis. Studies on the efficacy of DP2 receptor antagonists in various asthma phenotypes including: smokers, obese subjects, early vs late asthma onset, fixed vs reversible airflow limitation, are required for establishing their pharmacotherapeutic role.